Is High Maternal Body Mass Index Associated with Cesarean Section Delivery in Mongolia? A Prospective Observational Study - Naoko Hikita; Megumi Haruna; Masayo Matsuzaki; Emi Sasagawa; Minoru Murata; Ariunaa Yura; Otgontogoo Oidovsuren (Asian/Pacific Island Nursing Journal, 2019)
More than half of women are reported to be overweight or obese in Mongolia, thus becoming a big health issue. Though maternal obesity is a known risk factor for cesarean section (CS), it remains unclear how much a high maternal body mass index (BMI) would influence the risk of CS among pregnant women in Mongolia. This study aimed to investigate whether a higher maternal BMI is related to CS delivery in Darkhan-Uul Province, Mongolia. Pregnant women at 20 weeks’ gestation or less who visited public health facilities for antenatal health checkups between November 2015 and January 2016 were recruited. Data were collected using self-administered questionnaires, body weight measurement, and medical records. In total, 508 pregnant women participated, and data from 336 women were analyzed. Multiple logistic regression analysis showed that higher maternal BMI at first antenatal care visit (adjusted odds ratio [AOR] = 1.102, p = .033), higher gestational weight gain (AOR = 1.111, p = .001), older maternal age (AOR = 1.076, p = .030), and gestational age at delivery (AOR = 0.765, p = .005) were associated with CS delivery. This study is the first to demonstrate that higher maternal BMI and higher gestational weight gain are associated with CS delivery in Mongolia. Moreover, older maternal age and lower gestational age at delivery were found to be associated with CS delivery. Preventing obesity among women is important not only from the viewpoint of prevention of lifestyle diseases but also from the obstetric point of view; it is important for medical personnel to communicate the importance of preventing obesity to all women in Mongolia.